Unilateral Sinonasal Disease: analysis of the clinical, radiological and pathological features - Salami, Azzam M.A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Unilateral sinonasal disease is commonly encountered during the practice of the otolaryngologists, the etiology include a wide variety of diseases ranging from simple acute inflammation to highly malignant diseases. The clinical, computed tomography and histopathology differs between inflammatory and neoplastic diseases. Patients and Methods: A prospective study carried out at the Otolaryngology department, Baghdad Medical City, Hospital of specialized surgeries between Jan.2007 to Nov.2008.The study involved 114 patients with symptoms and signs of unilateral sinonasal disease, a careful history, complete clinical examination and radiological investigations were done to all patients as well as flexible nasoendoscopic examination. Sinonasal surgery under general or local anaesthesia with histopathological examination of the removed tissues was done to all patients. Results: Chronic rhinosinusitis with or without nasal polyposis is the commonest cause of a unilateral sinonasal disease (33.3%), followed by antrochoanal polyp (20%) , mucor mycosis (16.7%), benign tumors (13.1%), allergic fungal sinusitis (9.6%) and then malignant tumors (7.6%) in that order. Male gender and the right side were predominant. Purulent discharge and foul odor were the commonest presenting symptoms under inflammatory conditions, while frequent epistaxis, facial swelling and exophthalmos were the main symptoms in neoplastic diseases. Calcifications were observed on CT scan mainly in patients with allergic fungal sinusitis, while bony erosion and destruction was detected in both malignant tumors as well as mucor mycosis, the pattern and extent of bony destruction is more sever in malignant tumors. Conclusion: Chronic rhinosinusitis with or without nasal polyposis is the commonest cause of unilateral sinonasal disease. History, clinical examination, endoscopic as well as radiological examinations are important to reach the diagnosis. However, histopathological confirmation remains obligatory.